A gold-palladium coated ultra-soft copper composite bonding wire and preparation method thereof
By covering the palladium transition layer and pure gold plating on the copper alloy matrix, and controlling the element distribution by using the vacuum directional solidification method, the problems of high hardness and easy oxidation of pure copper bonded wire are solved, achieving higher mechanical properties and lower packaging costs.
Patent Information
- Application Number
- CN202311764656.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-12-21
AI Technical Summary
Pure copper bonded wire has high hardness, easy oxidation, and poor chemical stability, which affects the reliability and packaging cost of bonded wire.
The gold-palladium-coated ultra-soft copper composite bonded wire was prepared by vacuum directional solidification method. By controlling the crystallization temperature and speed of the material, calcium, cerium and indium elements were distributed in dots in copper, thereby improving material density and mechanical properties.
It improves the mechanical properties and surface quality of the material, reduces the length of the heat-affected zone, avoids golf balls or strawberry balls in the bonded wire, enhances the reliability of the bonded wire and reduces the packaging cost.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bonding wire preparation, and in particular to a gold-palladium coated ultra-soft copper composite bonding wire and a preparation method thereof. Background Art
[0002] Bonding wire (also known as bonding wire) is the main connection method between the chip and the external packaging substrate and / or multilayer circuit board (PCB). The development trend of bonding wire, from the product direction, is mainly the wire diameter miniaturization, high floor life and high spool length; from the chemical composition, copper wire (including bare copper wire, palladium-plated copper wire, gold-flashed palladium-plated copper wire) has largely replaced gold wire in the semiconductor field, while silver wire and silver alloy wire have replaced gold wire in LED and some IC packaging applications. Due to the development requirements of miniaturization and thinning of electronic products, the semiconductor industry has responded by thinning the chip thickness (wafer thinning), packaging using chip stacking (die stacking), flip chip (flip chip), wafer level packaging (wafer level packaging), 2.5D and 3D packaging and other methods, but traditional bonding packaging (wire bonding) is still the mainstream packaging form.
[0003] Compared with traditional gold bonding wire, copper bonding wire has low material cost and obvious price advantage. The electrical conductivity, thermal conductivity and comprehensive mechanical properties of copper bonding wire are also better than those of gold bonding wire, and it can realize ultra-fine wire diameter bonding wire below 150μm and low arc bonding package. In work, the current signal transmitted by copper bonding wire is not easily distorted, which is conducive to the heat extraction of chip working, and the growth rate of copper-aluminum intermetallic compounds at the interface is slow, the reliability is high, and the chip device life is long. However, pure copper bonding wire has high hardness, is easy to oxidize, and has poorer chemical stability than gold bonding wire. In the process of forming free air balls, the oxidation of pure copper will affect the size and shape of the free air balls; at the same time, the recrystallization temperature of pure copper is low, the grain size of the free air balls formed is large and the heat affected zone (HAZ) is long, which affects the reliability of the bonding wire. Therefore, pure copper bonding wire needs to be processed to meet market demand. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a gold-palladium coated ultra-soft copper composite bonding wire and a preparation method thereof. The present invention adopts a vacuum directional solidification method to control the crystallization temperature and speed of the material so that the three elements of calcium, cerium and indium are distributed in the copper in a point-like and uniform manner, which makes the material density relatively high, and the surface quality is smooth and excellent after fine wire drawing. The phenomenon of golf ball, strawberry ball, etc. is avoided during wire welding, the mechanical properties of the material are increased, and the length of the heat affected zone is greatly reduced.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] A gold-palladium coated ultra-soft copper composite bonding wire takes a copper alloy as a base material, a palladium transition layer is coated on the surface of the copper alloy base, and then a pure gold plating layer is coated on the surface of the palladium layer. By weight percentage, the content of the copper alloy base is 93.8-98.2%, the content of palladium in the transition layer is 0.3-1.2%, and the content of gold in the surface layer is 1.5-5.0%. The copper alloy base is prepared by mixing copper-calcium alloy, copper-cerium alloy, copper-indium alloy and high-purity copper and then subjecting to vacuum melting.
[0007] Preferably, the total content of calcium, cerium and indium in the copper alloy matrix is ≤0.003wt%.
[0008] Preferably, in the copper alloy matrix, the content of calcium is 0.0001-0.0005wt%, the content of cerium is 0.0001-0.0008wt%, and the content of indium is 0.0001-0.0008wt%.
[0009] Preferably, the content of calcium in the copper-calcium alloy is 0.1-0.5 wt %, the content of cerium in the copper-cerium alloy is 0.1-0.8 wt %, and the content of indium in the copper-indium alloy is 0.1-0.8 wt %.
[0010] Preferably, the preparation method of the copper alloy matrix is as follows: a high-purity copper block, a copper-calcium alloy, a copper-cerium alloy and a copper-indium alloy are placed in a high-purity graphite crucible, and placed in a vacuum furnace of a pull-down continuous casting furnace, and vacuum-heated to 1150°C to 1350°C. After the material is completely melted, it is kept warm for 15min to 60min and electromagnetically stirred; after stirring, it is refined for 10min to 60min, and a directional solidification method is adopted, and the pulling speed is controlled at 30mm / min to 150mm / min, and a copper alloy matrix with a diameter of φ8mm is obtained by pull-down continuous casting.
[0011] Preferably, the purity of the high-purity copper block is ≥99.999%.
[0012] Preferably, the thickness of the palladium-plated layer is 1-2 μm.
[0013] Preferably, the thickness of the gold-plated layer is 1-2 μm.
[0014] The present invention also provides a method for preparing the above-mentioned gold-palladium coated ultra-soft copper composite bonding wire, comprising the following steps:
[0015] S1, placing the copper alloy substrate in a heat treatment furnace for heat preservation, stretching it into a wire with a diameter of φ1.0 mm after the first deep cryogenic treatment, and then placing it in a heat treatment furnace for heat preservation again, stretching it into a wire with a diameter of φ0.1 mm after the second deep cryogenic treatment, and then stretching it into a wire with a diameter of φ0.03 mm to φ0.08 mm;
[0016] S2. The obtained wire material is sequentially subjected to surface cleaning, palladium plating, annealing treatment, activation treatment, and gold plating, and then stretched into a bonding wire with a diameter of φ0.011 mm to φ0.050 mm, thereby obtaining a gold-palladium coated ultra-soft copper composite bonding wire.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The present invention eliminates the internal stress generated by melting and casting through deep cryogenic treatment, and makes the added calcium, cerium, indium and copper have a more complete solid solution, and the crystal arrangement direction is consistent, so that the coarse crystals inside the material are broken up, and the crystal arrangement direction is more consistent. At the same time, the solid solution between copper, calcium, cerium and indium atoms is more complete, and the atoms are more tightly bound, thereby improving the performance of the metal; through deep cryogenic treatment, the coarse crystals inside the material are broken up, and the material structure is refined, thereby increasing the toughness of the material; through deep cryogenic treatment, the residual stress inside the material is transformed, and the parts where the internal stress is concentrated inside the material produce plastic rheology. In the subsequent rewarming process, trace stress is generated on the vacant surface of the material. This trace stress can reduce the damage to the inside of the material, which is ultimately manifested as an improvement in the mechanical properties of the material.
[0019] (2) The present invention increases the mechanical properties of the material by adding three elements, calcium, cerium and indium, and greatly reduces the length of the heat-affected zone when packaging the welding wire. The heat-affected zone is shortened, and the arc shape of the wire after bonding is firm and the spherical shape is more regular.
[0020] (3) The base material used in the present invention is ultra-soft copper, and the material's push-pull force, anti-oxidation performance, and bonding performance can all meet the performance requirements of gold bonding wires. The cost is only 1 / 8-1 / 12 of that of gold bonding wires, greatly reducing the packaging cost.
[0021] (4) The present invention adopts a vacuum directional solidification method to control the crystallization temperature and speed of the material so that the three elements of calcium, cerium and indium are evenly distributed in the copper in a dotted manner, which makes the material density relatively high, and the surface quality is smooth and excellent after fine wire drawing, and the phenomenon of golf ball, strawberry ball, etc. is avoided during wire welding. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0023] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0024] The invention provides a gold-palladium coated ultra-soft copper composite bonding wire. The copper alloy is used as a base material, a palladium transition layer is coated on the surface of the copper alloy base, and then a pure gold plating layer is coated on the surface of the palladium layer. By weight percentage, the content of the copper alloy base is 93.8-98.2%, the content of palladium in the transition layer is 0.3-1.2%, and the content of gold in the surface layer is 1.5-5.0%. The copper alloy base is prepared by mixing copper-calcium alloy, copper-cerium alloy, copper-indium alloy and high-purity copper and then subjecting the mixture to vacuum smelting.
[0025] In some embodiments of the present invention, typically but not limiting, by weight percentage, the copper alloy matrix content is 95.8%, the palladium content is 1.2%, and the gold content is 3%; or the copper alloy matrix content is 95%, the palladium content is 1%, and the gold content is 4%; it can also be the copper alloy matrix content is 96.5%, the palladium content is 0.8%, and the gold content is 2.7%.
[0026] Preferably, the total content of calcium, cerium and indium in the copper alloy matrix is ≤0.003wt%;
[0027] Further preferably, in the copper alloy matrix: the calcium content is 0.0001-0.0005wt%, further preferably 0.0002-0.0004wt%; the cerium content is 0.0001-0.0008wt%, further preferably 0.0003-0.0006wt%; the indium content is 0.0001-0.0008wt%, further preferably 0.0003-0.0006wt%.
[0028] Preferably, the calcium content in the copper-calcium alloy is 0.1-0.5wt%. In some embodiments of the present invention, typically but not limiting, the calcium content in the copper-calcium alloy can be selected as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%.
[0029] Preferably, the content of cerium in the copper-cerium alloy is 0.1-0.8wt%. In some embodiments of the present invention, typically but not limiting, the content of cerium in the copper-cerium alloy can be selected as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%;
[0030] Preferably, the indium content in the copper-indium alloy is 0.1-0.8wt%. In some embodiments of the present invention, typically but not limiting, the indium content in the copper-indium alloy can be selected as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%.
[0031] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0032] S1. Preparation of copper-calcium alloy sheet
[0033] According to weight percentage, 0.1% to 0.5% of calcium and 99.9% to 99.5% of copper are respectively put into a high-purity graphite crucible, and then placed in a vacuum alloy furnace, and vacuum-heated to 1150° C. to 1350° C. After the materials are completely melted, high-purity argon gas is filled in for protection, and the temperature is kept for 20 minutes to 70 minutes. The alloy melt is poured into a graphite casting mold to obtain a block-shaped copper-calcium alloy ingot; and the copper alloy ingot is rolled into a sheet with a thickness of 0.1 mm to 0.5 mm in stages.
[0034] S2. Preparation of copper-cerium alloy sheet
[0035] According to the weight percentage, 0.1% to 0.8% of cerium and 99.9% to 99.2% of copper are respectively put into a high-purity graphite crucible, and then placed in a vacuum alloy furnace, and vacuum-heated to 1150° C. to 1350° C. After the materials are completely melted, high-purity argon gas is filled in for protection, and the heat is kept for 20 minutes to 90 minutes. The copper alloy melt is poured into a graphite casting mold to obtain a block-shaped copper-cerium alloy ingot; the alloy ingot is rolled into a sheet with a thickness of 0.1 mm to 0.5 mm in batches.
[0036] S3. Preparation of copper-indium alloy sheet
[0037] According to the weight percentage, 0.1% to 0.8% of indium and 99.9% to 99.2% of copper are respectively put into a high-purity graphite crucible, and then placed in a vacuum alloy furnace, and vacuumed and heated to 1150° C. to 1350° C. After the materials are completely melted, high-purity argon gas is filled in for protection, and the heat is kept for 20 minutes to 90 minutes. The alloy melt is poured into a graphite casting mold to obtain a block-shaped copper-indium alloy ingot; and the alloy ingot is rolled into a sheet with a thickness of 0.1 mm to 0.5 mm in stages.
[0038] S4. Preparation of copper alloy bars
[0039] According to weight percentage, copper blocks, copper-calcium alloy sheets, copper-cerium alloy sheets and copper-indium alloy sheets with a purity of ≥99.999% are placed in a high-purity graphite crucible, and then placed in a vacuum furnace of a pull-down continuous casting furnace, and vacuum-heated to 1150°C to 1350°C. After the materials are completely melted, they are kept warm for 15min to 60min, and electromagnetic stirring is performed. After stirring, they are refined for 10min to 60min. A directional solidification method is adopted, and the pulling speed is controlled at 30mm / min to 150mm / min. The copper alloy rods with a diameter of φ8mm are obtained by pull-down continuous casting.
[0040] S5. First cryogenic treatment: Place the φ8mm copper alloy rod in a heat treatment furnace, fill it with nitrogen protection, and keep it at 500℃~800℃ for 12h~24h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -40℃~-120℃; quickly place the copper alloy rod after insulation in a liquid at -40℃~-120℃ and keep it for 10s~20s for cryogenic treatment to eliminate the internal stress of the cast bad rod.
[0041] S6. Rough drawing: Roughly draw the φ8mm rod into a wire with a diameter of φ1.0mm.
[0042] S7. Second cryogenic treatment: Place the wire with a diameter of φ1.0mm in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 300℃~600℃ for 0.2h~1h; add acetone (with liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -30℃~-100℃; quickly place the copper alloy wire after insulation in a liquid at -30℃~-100℃ and keep it for 5s~10s for grain refinement cryogenic treatment, so as to eliminate the internal stress caused by rough stretching, and make the crystal structure of the copper alloy material further refined and arranged more densely.
[0043] S8, intermediate stretching: intermediate stretching the wire with a diameter of φ1.0 mm processed in step S8 into a wire with a diameter of φ0.1 mm.
[0044] S9, fine drawing: the wire with a diameter of φ0.1mm is finely drawn into a wire with a diameter of φ0.03mm~φ0.08mm.
[0045] S10, surface cleaning: the finely drawn wire with a diameter of φ0.03 mm to φ0.08 mm is first cleaned with a sodium hydroxide solution having a concentration of 5% to 10%, and then rinsed with deionized water and dried.
[0046] S11. Surface coating with palladium: Use special continuous electroplating equipment to plate palladium online on the surface of the cleaned wire with a diameter of φ0.03mm to φ0.08mm. The purity of the palladium used for electroplating is ≥99.99%. The wire-winding speed is 20m to 100m / min, the current is controlled at 0.15 to 0.5A, and the coating thickness is controlled at 1 to 2.0μm.
[0047] S12, process annealing treatment: Place the φ0.03mm~φ0.08mm palladium-plated wire in a continuous annealing system, use high-purity nitrogen as a protective gas, temperature 300℃~600℃, speed 40m~80m / min for continuous process annealing treatment, further reduce the hardness of the material and improve the toughness of the material.
[0048] S13, activation treatment: the φ0.03mm~φ0.08mm wire after process annealing is placed in a continuous activation treatment system, the wire is passed through an activation acid solution with a concentration of 2%~8%, the solution temperature is 50℃~100℃, and the running speed is 40m~80m / min for activation treatment, and the wire is dried during winding, and the drying temperature is 100℃~120℃, so as to completely remove the microscopic carbon deposits caused by the high temperature of the residual lubricating liquid on the surface of the wire during the annealing process.
[0049] S14, Surface gold coating: Use special continuous electroplating equipment to gold-plate the surface of the activated φ0.03mm~φ0.08mm wire online. The purity of the gold used for electroplating is ≥99.99%. The wire-winding speed is 20m~100m / min, the current is controlled at 0.2~0.6A, and the coating thickness is controlled at 1~2.0μm.
[0050] S15, micro-stretching: micro-stretching the wire with a diameter of φ0.03mm to φ0.08mm to form a composite bonding wire with a diameter of φ0.011mm to φ0.050mm.
[0051] S16, finished product annealing treatment: Place the composite bonding wire of φ0.011mm~φ0.05mm in a continuous annealing system, use high-purity nitrogen as the protective gas, temperature 300℃~700℃, speed 40m~100m / min for continuous annealing treatment to achieve the breaking force and elongation required by customers.
[0052] S17, rewinding and packaging: the silk thread processed in step S16 is rolled into a fixed length, the tension is controlled to be 0.5g-8.0g, and the length of a single roll is 500m or 1000m.
[0053] The present invention will be further described below by means of specific examples.
[0054] Example 1
[0055] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0056] S1. Place 1994g of copper block, 2g of copper-calcium alloy sheet, 2g of copper-cerium alloy sheet and 2g of copper-indium alloy sheet in a vacuum furnace of a pull-down continuous casting furnace, evacuate and heat to 1200°C, and after the material is completely melted, keep warm for 30min, perform electromagnetic stirring, and refine for 30min after stirring. Use a directional solidification method and control the pulling speed at 100mm / min to prepare a copper alloy matrix rod with a diameter of φ8.0mm;
[0057] The calcium content in the copper-calcium alloy sheet is 0.5wt%, the cerium content in the copper-cerium alloy sheet is 0.4wt%, the indium content in the copper-indium alloy sheet is 0.5wt%, and the thickness of the copper-calcium alloy sheet, copper-cerium alloy sheet, and copper-indium alloy sheet are all 0.3mm.
[0058] S2. Place a φ8mm copper alloy matrix rod in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 600℃ for 12h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -60℃; quickly place the copper alloy rod after insulation in a liquid at -60℃ and keep it for 15s for deep cryogenic treatment to eliminate the internal stress of the bad cast rod, and stretch it into a wire with a diameter of φ1.0mm after the first deep cryogenic treatment, and then place it in a heat treatment furnace again and keep it warm at 450℃ for 12h, and quickly place the copper alloy wire after insulation in a liquid at -60℃ and keep it for 10s for grain refinement deep cryogenic treatment, and then stretch it into a wire with a diameter of φ0.1mm, and continue to stretch it into a wire with a diameter of φ0.06mm.
[0059] S3. The obtained wire is cleaned with a 10wt% sodium hydroxide solution, plated with palladium, placed in a continuous annealing system, and subjected to continuous process annealing treatment at a temperature of 400°C and a speed of 50m / min using high-purity nitrogen as a protective gas. The wire is placed in a continuous activation treatment system, and the wire is passed through a 6wt% citric acid solution at a solution temperature of 80°C and a running speed of 60m / min for activation treatment, gold-plated, and then stretched into a composite bonding wire with a diameter of φ0.030mm.
[0060] In this embodiment, the content of the copper alloy matrix is 95wt%, the content of palladium in the transition layer is 0.8wt%, and the content of gold in the surface layer is 4.2wt%.
[0061] Example 2
[0062] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0063] S1. Place 1994g of copper block, 2g of copper-calcium alloy sheet, 2g of copper-cerium alloy sheet and 2g of copper-indium alloy sheet in a vacuum furnace of a pull-down continuous casting furnace, evacuate and heat to 1200°C, and after the material is completely melted, keep warm for 30min, perform electromagnetic stirring, and refine for 30min after stirring. Use a directional solidification method and control the pulling speed at 100mm / min to prepare a copper alloy matrix rod with a diameter of φ8.0mm;
[0064] The calcium content in the copper-calcium alloy sheet is 0.3wt%, the cerium content in the copper-cerium alloy sheet is 0.6wt%, the indium content in the copper-indium alloy sheet is 0.5wt%, and the thickness of the copper-calcium alloy sheet, copper-cerium alloy sheet, and copper-indium alloy sheet are all 0.3mm.
[0065] S2. Place a φ8mm copper alloy matrix rod in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 600℃ for 12h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -60℃; quickly place the copper alloy rod after insulation in a liquid at -60℃ and keep it for 15s for deep cryogenic treatment to eliminate the internal stress of the bad cast rod, and stretch it into a wire with a diameter of φ1.0mm after the first deep cryogenic treatment, and then place it in a heat treatment furnace again and keep it warm at 450℃ for 12h, and quickly place the copper alloy wire after insulation in a liquid at -60℃ and keep it for 10s for grain refinement deep cryogenic treatment, and then stretch it into a wire with a diameter of φ0.1mm, and continue to stretch it into a wire with a diameter of φ0.06mm.
[0066] S3. The obtained wire is cleaned with a 10wt% sodium hydroxide solution, plated with palladium, placed in a continuous annealing system, and subjected to continuous process annealing treatment at a temperature of 400°C and a speed of 50m / min using high-purity nitrogen as a protective gas. The wire is placed in a continuous activation treatment system, and the wire is passed through a 6wt% citric acid solution at a solution temperature of 80°C and a running speed of 60m / min for activation treatment, gold-plated, and then stretched into a composite bonding wire with a diameter of φ0.030mm.
[0067] In this embodiment, the content of the copper alloy matrix is 96.2wt%, the content of palladium in the transition layer is 0.8wt%, and the content of gold in the surface layer is 3.0wt%.
[0068] Example 3
[0069] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0070] S1. Place 1994g of copper block, 2g of copper-calcium alloy sheet, 2g of copper-cerium alloy sheet and 2g of copper-indium alloy sheet in a vacuum furnace of a pull-down continuous casting furnace, evacuate and heat to 1200°C, and after the material is completely melted, keep warm for 30min, perform electromagnetic stirring, and refine for 30min after stirring. Use a directional solidification method and control the pulling speed at 100mm / min to prepare a copper alloy matrix rod with a diameter of φ8.0mm;
[0071] The calcium content in the copper-calcium alloy sheet is 0.4wt%, the cerium content in the copper-cerium alloy sheet is 0.6wt%, the indium content in the copper-indium alloy sheet is 0.8wt%, and the thickness of the copper-calcium alloy sheet, copper-cerium alloy sheet, and copper-indium alloy sheet are all 0.3mm.
[0072] S2. Place a φ8mm copper alloy matrix rod in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 600℃ for 12h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -60℃; quickly place the copper alloy rod after insulation in a liquid at -60℃ and keep it for 15s for deep cryogenic treatment to eliminate the internal stress of the bad cast rod, and stretch it into a wire with a diameter of φ1.0mm after the first deep cryogenic treatment, and then place it in a heat treatment furnace again and keep it warm at 450℃ for 12h, and quickly place the copper alloy wire after insulation in a liquid at -60℃ and keep it for 10s for grain refinement deep cryogenic treatment, and then stretch it into a wire with a diameter of φ0.1mm, and continue to stretch it into a wire with a diameter of φ0.06mm.
[0073] S3. The obtained wire is cleaned with a 10wt% sodium hydroxide solution, plated with palladium, placed in a continuous annealing system, and subjected to continuous process annealing treatment at a temperature of 400°C and a speed of 50m / min using high-purity nitrogen as a protective gas. The wire is placed in a continuous activation treatment system, and the wire is passed through a 6wt% citric acid solution at a solution temperature of 80°C and a running speed of 60m / min for activation treatment, gold-plated, and then stretched into a composite bonding wire with a diameter of φ0.030mm.
[0074] In this embodiment, the content of the copper alloy matrix is 93.8wt%, the content of palladium in the transition layer is 1.2wt%, and the content of gold in the surface layer is 5.0wt%.
[0075] Example 4
[0076] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0077] S1. Place 1994g of copper block, 2g of copper-calcium alloy sheet, 2g of copper-cerium alloy sheet and 2g of copper-indium alloy sheet in a vacuum furnace of a pull-down continuous casting furnace, evacuate and heat to 1200°C, and after the material is completely melted, keep warm for 30min, perform electromagnetic stirring, and refine for 30min after stirring. Use a directional solidification method and control the pulling speed at 100mm / min to prepare a copper alloy matrix rod with a diameter of φ8.0mm;
[0078] The calcium content in the copper-calcium alloy sheet is 0.5wt%, the cerium content in the copper-cerium alloy sheet is 0.5wt%, the indium content in the copper-indium alloy sheet is 0.8wt%, and the thickness of the copper-calcium alloy sheet, copper-cerium alloy sheet, and copper-indium alloy sheet are all 0.3mm.
[0079] S2. Place a φ8mm copper alloy matrix rod in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 600℃ for 12h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -60℃; quickly place the copper alloy rod after insulation in a liquid at -60℃ and keep it for 15s for deep cryogenic treatment to eliminate the internal stress of the bad cast rod, and stretch it into a wire with a diameter of φ1.0mm after the first deep cryogenic treatment, and then place it in a heat treatment furnace again and keep it warm at 450℃ for 12h, and quickly place the copper alloy wire after insulation in a liquid at -60℃ and keep it for 10s for grain refinement deep cryogenic treatment, and then stretch it into a wire with a diameter of φ0.1mm, and continue to stretch it into a wire with a diameter of φ0.06mm.
[0080] S3. The obtained wire is cleaned with a 10wt% sodium hydroxide solution, plated with palladium, placed in a continuous annealing system, and subjected to continuous process annealing treatment at a temperature of 400°C and a speed of 50m / min using high-purity nitrogen as a protective gas. The wire is placed in a continuous activation treatment system, and the wire is passed through a 6wt% citric acid solution at a solution temperature of 80°C and a running speed of 60m / min for activation treatment, gold-plated, and then stretched into a composite bonding wire with a diameter of φ0.030mm.
[0081] In this embodiment, the content of the copper alloy matrix is 98.2wt%, the content of palladium in the transition layer is 0.3wt%, and the content of gold in the surface layer is 1.5wt%.
[0082] Comparative Example 1
[0083] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0084] S1. Place copper blocks, calcium, cerium and indium in a vacuum furnace of a pull-down continuous casting furnace, evacuate and heat to 1200°C, and after the materials are completely melted, keep warm for 30 minutes, perform electromagnetic stirring, and refine for 30 minutes after stirring. Use a directional solidification method and control the pulling speed at 100 mm / min to prepare a copper alloy matrix rod with a diameter of φ8.0 mm;
[0085] The copper alloy matrix rod has a calcium content of 0.0004wt%, a cerium content of 0.0006wt%, and an indium content of 0.0008wt%.
[0086] S2. Place a φ8mm copper alloy matrix rod in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 600℃ for 12h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -60℃; quickly place the copper alloy rod after insulation in a liquid at -60℃ and keep it for 15s for deep cryogenic treatment to eliminate the internal stress of the bad cast rod, and stretch it into a wire with a diameter of φ1.0mm after the first deep cryogenic treatment, and then place it in a heat treatment furnace again and keep it warm at 450℃ for 12h, and quickly place the copper alloy wire after insulation in a liquid at -60℃ and keep it for 10s for grain refinement deep cryogenic treatment, and then stretch it into a wire with a diameter of φ0.1mm, and continue to stretch it into a wire with a diameter of φ0.06mm.
[0087] S3. The obtained wire is cleaned with a 10wt% sodium hydroxide solution, plated with palladium, placed in a continuous annealing system, and subjected to continuous process annealing treatment at a temperature of 400°C and a speed of 50m / min using high-purity nitrogen as a protective gas. The wire is placed in a continuous activation treatment system, and the wire is passed through a 6wt% citric acid solution at a solution temperature of 80°C and a running speed of 60m / min for activation treatment, gold-plated, and then stretched into a composite bonding wire with a diameter of φ0.030mm.
[0088] The content of the copper alloy matrix is 93.8wt%, the content of palladium in the transition layer is 1.2wt%, and the content of gold in the surface layer is 5.0wt%.
[0089] Comparative Example 2
[0090] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0091] S1. Place 1996g of copper block, 2g of copper-cerium alloy sheet and 2g of copper-indium alloy sheet in a vacuum furnace of a pull-down continuous casting furnace, evacuate and heat to 1200°C, and after the material is completely melted, keep warm for 30min, perform electromagnetic stirring, and refine for 30min after stirring. Use a directional solidification method and control the pulling speed at 100mm / min to prepare a copper alloy matrix rod with a diameter of φ8.0mm;
[0092] The cerium content in the copper-cerium alloy sheet is 0.6wt%, the indium content in the copper-indium alloy sheet is 0.8wt%, and the thickness of the copper-cerium alloy sheet and the copper-indium alloy sheet are both 0.3mm.
[0093] S2. Place a φ8mm copper alloy matrix rod in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 600℃ for 12h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -60℃; quickly place the copper alloy rod after insulation in a liquid at -60℃ and keep it for 15s for deep cryogenic treatment to eliminate the internal stress of the bad cast rod, and stretch it into a wire with a diameter of φ1.0mm after the first deep cryogenic treatment, and then place it in a heat treatment furnace again and keep it warm at 450℃ for 12h, and quickly place the copper alloy wire after insulation in a liquid at -60℃ and keep it for 10s for grain refinement deep cryogenic treatment, and then stretch it into a wire with a diameter of φ0.1mm, and continue to stretch it into a wire with a diameter of φ0.06mm.
[0094] S3. The obtained wire is cleaned with a 10wt% sodium hydroxide solution, plated with palladium, placed in a continuous annealing system, and subjected to continuous process annealing treatment at a temperature of 400°C and a speed of 50m / min using high-purity nitrogen as a protective gas. The wire is placed in a continuous activation treatment system, and the wire is passed through a 6wt% citric acid solution at a solution temperature of 80°C and a running speed of 60m / min for activation treatment, gold-plated, and then stretched into a composite bonding wire with a diameter of φ0.030mm.
[0095] The content of the copper alloy matrix is 93.8wt%, the content of palladium in the transition layer is 1.2wt%, and the content of gold in the surface layer is 5.0wt%.
[0096] Comparative Example 3
[0097] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0098] S1. Place 1996g of copper block, 2g of copper-calcium alloy sheet and 2g of copper-indium alloy sheet in a vacuum furnace of a pull-down continuous casting furnace, evacuate and heat to 1200°C, and after the material is completely melted, keep warm for 30min, perform electromagnetic stirring, and refine for 30min after stirring. Use a directional solidification method and control the pulling speed at 100mm / min to prepare a copper alloy matrix rod with a diameter of φ8.0mm;
[0099] The calcium content in the copper-calcium alloy sheet is 0.4wt%, the indium content in the copper-indium alloy sheet is 0.8wt%, and the thickness of the copper-calcium alloy sheet and the copper-indium alloy sheet are both 0.3mm.
[0100] S2. Place a φ8mm copper alloy matrix rod in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 600℃ for 12h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -60℃; quickly place the copper alloy rod after insulation in a liquid at -60℃ and keep it for 15s for deep cryogenic treatment to eliminate the internal stress of the bad cast rod, and stretch it into a wire with a diameter of φ1.0mm after the first deep cryogenic treatment, and then place it in a heat treatment furnace again and keep it warm at 450℃ for 12h, and quickly place the copper alloy wire after insulation in a liquid at -60℃ and keep it for 10s for grain refinement deep cryogenic treatment, and then stretch it into a wire with a diameter of φ0.1mm, and continue to stretch it into a wire with a diameter of φ0.06mm.
[0101] S3. The obtained wire is cleaned with a 10wt% sodium hydroxide solution, plated with palladium, placed in a continuous annealing system, and subjected to continuous process annealing treatment at a temperature of 400°C and a speed of 50m / min using high-purity nitrogen as a protective gas. The wire is placed in a continuous activation treatment system, and the wire is passed through a 6wt% citric acid solution at a solution temperature of 80°C and a running speed of 60m / min for activation treatment, gold-plated, and then stretched into a composite bonding wire with a diameter of φ0.030mm.
[0102] The content of the copper alloy matrix is 93.8wt%, the content of palladium in the transition layer is 1.2wt%, and the content of gold in the surface layer is 5.0wt%.
[0103] Comparative Example 4
[0104] A method for preparing a gold-palladium coated ultra-soft copper composite bonding wire comprises the following steps:
[0105] S1. Place 1996g of copper block, 2g of copper-calcium alloy sheet and 2g of copper-cerium alloy sheet in a vacuum furnace of a pull-down continuous casting furnace, evacuate and heat to 1200°C, and after the material is completely melted, keep warm for 30min, perform electromagnetic stirring, and refine for 30min after stirring. Use a directional solidification method and control the pulling speed at 100mm / min to prepare a copper alloy matrix rod with a diameter of φ8.0mm;
[0106] The calcium content in the copper-calcium alloy sheet is 0.4wt%, the cerium content in the copper-cerium alloy sheet is 0.6wt%, and the thickness of the copper-calcium alloy sheet and the copper-cerium alloy sheet are both 0.3mm.
[0107] S2. Place a φ8mm copper alloy matrix rod in a heat treatment furnace, fill it with nitrogen protection, and keep it warm at 600℃ for 12h; add acetone (to liquid nitrogen in a volume ratio of 1:3) into a special container, and inject liquid nitrogen, and control the temperature at -60℃; quickly place the copper alloy rod after insulation in a liquid at -60℃ and keep it for 15s for deep cryogenic treatment to eliminate the internal stress of the bad cast rod, and stretch it into a wire with a diameter of φ1.0mm after the first deep cryogenic treatment, and then place it in a heat treatment furnace again and keep it warm at 450℃ for 12h, and quickly place the copper alloy wire after insulation in a liquid at -60℃ and keep it for 10s for grain refinement deep cryogenic treatment, and then stretch it into a wire with a diameter of φ0.1mm, and continue to stretch it into a wire with a diameter of φ0.06mm.
[0108] S3. The obtained wire is cleaned with a 10wt% sodium hydroxide solution, plated with palladium, placed in a continuous annealing system, and subjected to continuous process annealing treatment at a temperature of 400°C and a speed of 50m / min using high-purity nitrogen as a protective gas. The wire is placed in a continuous activation treatment system, and the wire is passed through a 6wt% citric acid solution at a solution temperature of 80°C and a running speed of 60m / min for activation treatment, gold-plated, and then stretched into a composite bonding wire with a diameter of φ0.030mm.
[0109] The content of the copper alloy matrix is 93.8wt%, the content of palladium in the transition layer is 1.2wt%, and the content of gold in the surface layer is 5.0wt%.
[0110] The composite bonding wires prepared in Example 3 and Comparative Examples 1-4 were subjected to performance tests, and the test results are shown in the following table:
[0111] Breaking force(g) Elongation(%) HAZ length (μm) Example 3 6.42 12.66 44 Comparative Example 1 4.83 13.82 67 Comparative Example 2 5.57 13.48 56 Comparative Example 3 5.84 12.95 59 Comparative Example 4 5.68 13.21 61
[0112] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A gold-palladium coated ultra-soft copper composite bonding wire, characterized in that: A copper alloy is used as a base material, a palladium transition layer is coated on the surface of the copper alloy base, and then a pure gold plating layer is coated on the surface of the palladium layer. By weight percentage, the content of the copper alloy base is 93.8-98.2%, the content of palladium in the transition layer is 0.3-1.2%, and the content of gold in the surface layer is 1.5-5.0%, wherein the copper alloy base is prepared by mixing copper-calcium alloy, copper-cerium alloy, copper-indium alloy and high-purity copper and then subjected to vacuum melting; The total content of calcium, cerium and indium in the copper alloy matrix is ≤ 0.003wt%; In the copper alloy matrix: the content of calcium is 0.0001-0.0005wt%, the content of cerium is 0.0001-0.0008wt%, and the content of indium is 0.0001-0.0008wt%; The content of calcium in the copper-calcium alloy is 0.1-0.5wt%, the content of cerium in the copper-cerium alloy is 0.1-0.8wt%, and the content of indium in the copper-indium alloy is 0.1-0.8wt%; The preparation method of the copper alloy matrix is as follows: a high-purity copper block, a copper-calcium alloy, a copper-cerium alloy and a copper-indium alloy are placed in a high-purity graphite crucible, and placed in a vacuum furnace of a pull-down continuous casting furnace, and vacuum-heated to 1150° C. to 1350° C., and after the material is completely melted, the material is kept warm for 15 min to 60 min, and electromagnetic stirring is performed; after stirring, the material is refined for 10 min to 60 min, and a directional solidification method is adopted, and the pulling speed is controlled at 30 mm / min to 150 mm / min, and the copper alloy matrix with a diameter of φ8 mm is obtained by pull-down continuous casting; The purity of high purity copper block is ≥99.999%.
2. The gold-palladium coated ultra-soft copper composite bonding wire according to claim 1, characterized in that: The thickness of the palladium layer is 1-2 μm.
3. The gold-palladium coated ultra-soft copper composite bonding wire according to claim 1, characterized in that: The thickness of the gold-plated layer is 1-2 μm.
4. The method for preparing the gold-palladium coated ultra-soft copper composite bonding wire according to any one of claims 1 to 3, characterized in that: The steps include: S1, placing the copper alloy substrate in a heat treatment furnace for heat preservation, stretching it into a wire with a diameter of φ1.0 mm after the first deep cryogenic treatment, and then placing it in a heat treatment furnace for heat preservation again, stretching it into a wire with a diameter of φ0.1 mm after the second deep cryogenic treatment, and then stretching it into a wire with a diameter of φ0.03 mm to φ0.08 mm; S2. The obtained wire material is sequentially subjected to surface cleaning, palladium plating, annealing treatment, activation treatment, and gold plating, and then stretched into a bonding wire with a diameter of φ0.011 mm to φ0.050 mm, thereby obtaining a gold-palladium coated ultra-soft copper composite bonding wire.
Citation Information
Patent Citations
Alloy-doped gold bonding wire and cryogenic-treatment preparation method thereof
CN106011516A
Thin cold and copper alloy wire and manufacturing method thereof
CN108122877A